2016
DOI: 10.1093/jac/dkw015
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous drug resistance detection and genotyping ofMycobacterium tuberculosisusing a low-density hydrogel microarray

Abstract: The developed test has a high sensitivity and specificity and can be directly applied to clinical samples. The combination of mutation-based drug resistance profiling and basic genotyping could be useful for clinical microbiology studies and epidemiological surveillance of the M. tuberculosis complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 65 publications
0
18
0
2
Order By: Relevance
“…The model was used to predict hybridization kinetics of eighteen 20-mer probes targeting vancomycin resistant genes. This gene was chosen as a model because emergence of antibiotic resistance associated with pathogenic bacteria is an alarming global issue [14,15] and numerous hybridization-based biochip platforms are being developed to diagnose multi-drug resistant bacteria [16,17,18,19,20]. Effect of target concentration, temperature, recirculation flow rate and rate constants on the hybridization kinetics, with target concentration, rate constants, and temperature being the most important parameters affecting the rate of hybridization were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The model was used to predict hybridization kinetics of eighteen 20-mer probes targeting vancomycin resistant genes. This gene was chosen as a model because emergence of antibiotic resistance associated with pathogenic bacteria is an alarming global issue [14,15] and numerous hybridization-based biochip platforms are being developed to diagnose multi-drug resistant bacteria [16,17,18,19,20]. Effect of target concentration, temperature, recirculation flow rate and rate constants on the hybridization kinetics, with target concentration, rate constants, and temperature being the most important parameters affecting the rate of hybridization were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we performed the Sensititre MycoTB alongside the Bactec MGIT 960 and identified common mutations leading to drug resistance using the microarray-based method [20] with clinical isolates from the Moscow region. The selected strains had a strong bias toward drug resistance; nevertheless, a drastic difference in the MDR and XDR prevalence rates was observed in patients with a history of previous treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the TB-TEST assay application for the analysis of clinical material largely depended on the number of mycobacterial cells in the sample similar to any other molecular method. The TB-TEST works correctly with 96% of AFB-positive and 25% of AFB-negative clinical samples [20]. Thus, in the case of the failure of the direct genetic analysis of a clinical sample, a short-term liquid culture could be used with the Bactec MGIT automated system, and the obtained DNA from the isolate could be re-assayed using the TB-TEST.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations